Solubility and Spectral Studies of Dilute COS in Ethylene Glycol + Water System - Li, Wenxiu; Liu, Quansheng; An, Shengli; Yuan, Xufang; Ma, Yue (Asian Journal of Chemistry, 2011)
In this work, the solubility data have been measured for COS + N2 mixture gases in the aqueous solutions of ethylene glycol in the range of (298.15-318.15) K. Measurements were carried out by a saturation method using a glass absorption apparatus, which were controlled at constant temperatures using a thermostatic circulation bath with Beckmann thermometer. The solubility data were obtained with relative uncertainties within ± 3.5 % for COS concentration in gas phase. The measurement showed that the addition of water to ethylene glycol enhanced the solubility of dilute COS compared with pure ethylene glycol and that the 50 % volume fraction of ethylene glycol in aqueous solution of ethylene glycol (mass fraction is 52.24 %) is a more reasonable composition used in absorption processes of COS. When conventional UV, FTIR, fluorescence and 1H NMR spectroscopic techniques were used for inspection of spectral changes of COS in aqueous solutions of ethylene glycol, the spectral results suggest that COS can interact with ethylene glycol by hydrogen bonding and interaction. The results of this work can be used to provide important data for the design and operation of the absorption and desorption processes of COS with potential industrial application of aqueous solutions of ethylene glycol.